Batch extraction of gossypol from cottonseed meal using mixed solvent system and its kinetic modeling. Issue 12 (2nd December 2019) - Singh, Surinder; Sharma, S. K.; Kansal, S. K.
Abstract: Batch extraction of gossypol, a known toxic pigment present in cottonseed was carried out using a green and mixed solvent system comprising butanol–ethanol–water (80:15:5 v/v). The cottonseed was defatted, that is, oil from seeds was removed prior to gossypol extraction and parameters affecting the extraction were optimized. The kinetic parameters namely initial extraction rate, rate constant of extraction, and extraction capacity were evaluated and extraction of gossypol was found to be influenced by increase in temperature. Maximum extraction of gossypol (94.73%) occurred using butanol–ethanol–water mixed solvent acidified with 0.5 M oxalic acid, at solvent to seed ratio of 15, in extraction time of 180 min, and a temperature of 348 K. The activation energy of extraction was also determined and was found out to be 9.60 kJ mol −1 . Thermodynamic parameters, for example, Gibbs free energy, enthalpy, and entropy were also evaluated which showed that extraction process was spontaneous, endothermic in nature, and irreversible. The mixed solvent system utilized showed high potential to extract gossypol from cottonseed.